Enhancing Students Writing Ability In Recount Text Using Picture Series - Aniq, Muhammad; Senowarsito, Senowarsito (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2023)
Language serves as a communication system utilized by communities or nations, comprising various symbols and non-verbal signs. Listening, speaking, reading, and writing are the four core language skills. Among these, writing is often considered challenging by students as it necessitates the ability to express ideas, thoughts, and emotions in written form. In the context of English language education in junior high schools, comprehension and production of functional texts and monologues, such as descriptive essays, recounts, narratives, procedures, and reports, are essential components. This study explores the use of Picture Series as a learning tool with a discovery learning model to enhance students’ writing abilities in English, specifically focusing on the "Recount Text" material in Class VIII E of SMP Negeri 36 Semarang. The research employs the Classroom Action Research (CAR) method consisting of two cycles. The research results reveal that the improvements made in the second cycle successfully enhanced students’ writing skills. In the pre-cycle, only around 18.75% of students achieved the Minimum Completion Criteria (KKM), but in the first cycle, around 71.88% then in the second cycle reached 87.5% of students who succeeded in achieving the expected competency level. Observations of students’ activities also indicate significant progress in the second cycle, with students being more actively engaged in developing and presenting ideas, as well as providing and receiving feedback. This research affirms that the learning approach using the discovery learning model with the utilization of Picture Series is effective in improving students’ writing skills in English. These findings have implications for teachers and schools in enhancing the quality of education, improving teacher competence, and, overall, elevating the educational standards in schools.